Development of Virtual Reality Learning Media on Kinematics Material Based on the Kuula Platform Assisted by Google Classroom to Improve Conceptual Understanding of Grade X Students - Deki Saputra; Eko Risdianto; Fitri April Yanti; Sultan Hammad Alshammari; Hamed Barjesteh; Andik Purwanto (CV. Media Inti Teknologi, 2026)
Background: Physics learning, particularly in Kinematics material, often faces constraints due to the abstract nature of its concepts and limited laboratory facilities in schools. This potentially reduces students' conceptual understanding and learning engagement.Aims: To develop 360° video-based VR learning media utilizing the Kuula platform assisted by Google Classroom, and to analyze its feasibility, usefulness and efficiency in enhancing the conceptual understanding of Kinematics among Grade X students in their senior year of high school.Methods: This study employed the ADDIE paradigm (Analysis, Design, Development, Implementation, Evaluation) in conjunction with the Research and Development (R&D) technique. Techniques for gathering data included (1) expert validation sheets assessed by 2 physics lecturers and 1 physics teacher, (2) practicality response questionnaires filled out by 36 students, and (3) a conceptual understanding test in the form of pre-test and post-test. The test data were then analyzed by calculating the normalized N-Gain score to determine the effectiveness of the developed product.Results: Expert validation results showed a percentage of 89% (highly feasible category). Student responses regarding the practicality of the media obtained an average of 86% (very good). An N-Gain score of 85% indicated an improvement in conceptual understanding classified as